2007
DOI: 10.1002/lapl.200710004
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman spectroscopy for the detection of carotenoids in foodstuffs. Influence of the nutrition on the antioxidative potential of the skin

Abstract: Various fruit, vegetables and plants contain a high amount of carotenoids such as beta-carotene, lycopene, lutein, zeaxanthin, and other antioxidants in different concentrations and combinations. These substances used by nature are an effective defense mechanism against the destructive action of free radicals, which are the result of the negative influence of the environment. It was found that the peel of fruit and vegetables usually contains a higher amount of carotenoids than the pulp. Humans cannot synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 15 publications
2
66
0
Order By: Relevance
“…The results of the study demonstrated that carotenoids taken up by consuming fruit and vegetables are rarely accumulated in the human skin. These results are in agreement with results showing an increase in carotenoid concentration in the skin and blood after a supplementation rich in carotenoids [74][75][76][77][78][79][80][81][82] .…”
Section: Lifestyle Conditionssupporting
confidence: 82%
See 1 more Smart Citation
“…The results of the study demonstrated that carotenoids taken up by consuming fruit and vegetables are rarely accumulated in the human skin. These results are in agreement with results showing an increase in carotenoid concentration in the skin and blood after a supplementation rich in carotenoids [74][75][76][77][78][79][80][81][82] .…”
Section: Lifestyle Conditionssupporting
confidence: 82%
“…It was found that the concentration of the antioxidants correlated with the lifestyle of the volunteers [4] . Individuals with a healthy diet, rich in fruit and vegetables, had higher carotenoid concentrations than the other volunteers, who were smokers and/or only consumed a low amount of fruit and vegetables [4,52,74] . The results obtained there are in agreement with the results obtained by other groups [75,76] .…”
Section: Lifestyle Conditionsmentioning
confidence: 99%
“…[12][13][14][15] In a number of studies, it was shown that the nutrition influences the values, [16][17][18][19][20][21] whereby stress, in form of sun irradiation, illness or the lack of sleep, reduces the values. [20,22,23] However, up to now, no systematic study about the concentration and distribution of the carotenoids in a representative healthy group of the population has been performed.…”
Section: Wwwantioxorgmentioning
confidence: 99%
“…A recently conducted study clearly revealed that stress fac-tors -such as irradiation, environmental conditions, illness, inflammation, smoking and alcohol consumption -also produce free radicals in human skin, and thus may decrease the antioxidant levels of the skin [8,[50][51][52][53][54] . Consequently, a balanced nutritional intake -rich, for instance, in fruit and vegetables, where the antioxidants are naturally balanced -is able to increase the antioxidant levels of the skin [32,55] . Therefore, high amounts of antioxidants in the human skin act as an efficient anti-aging strategy, as recently demonstrated [56] .…”
Section: Antioxidants As An Anti-aging Strategymentioning
confidence: 99%